Nonscrotal Causes of Acute Scrotum. (13th August 2020) - Campo, Irene; Valentino, Massimo; Sidhu, Paul S.; Magi Meconi, Luca; Van Nieuwenhove, Sandy; Cova, Maria Assunta; Derchi, Lorenzo E.; Bertolotto, Michele
Abstract : Acute scrotum is characterized by intense acute scrotal pain, which may be associated with other symptoms and signs such as abdominal pain, inflammation, and fever. Many pathologic conditions can present in this way, most which involve the scrotal contents. Nonscrotal conditions, however, can rarely present clinically only as acute scrotum: among them, renal colic, aneurysm rupture or other causes of retroperitoneal hemorrhage, primary abdominal or pelvic tumors and metastases, pancreatitis, pelvic inflammation, and muscle injuries. The pathophysiologic characteristics of the clinical presentation, clues for diagnosis, and imaging features of a series of nonscrotal lesions presenting clinically with acute scrotal pain are herein reported and illustrated. In patients presenting with acute scrotal symptoms and normal scrotal ultrasound findings, nonscrotal causes of acute scrotal pain should be considered in the differential diagnosis. Therefore, an ultrasound investigation of the abdomen, groin, and thighs is indicated.